Pemberdayaan Kelompok Tani Hutan Palasari Melalui Bongsang Berbasis Bambu - Sri Wilujeng; Ina Darliana1; Ishak Tan; Reni Srimulyaningsih (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Community empowerment through the utilization of non-timber forest products is an important strategy to support sustainable forest management and improve local livelihoods. Bamboo is a promising resource that can be processed into value-added handicraft products, such as bongsang. The object of this community service program to improve the capacity of the Palasari Forest Farmer Group through training in bamboo-based bongsang production. The program was implemented using a participatory approach combining counselling and hands-on practice, involving 16 participants. Its effectiveness was evaluated using pre-test and post-test questionnaires with a four-point Likert scale covering knowledge, attitudes and motivation, skills, and perceptions of bamboo potential. Data were analysed using descriptive percentage analysis. The results showed that the average score increased from 67.7% before the activity to 78.1% after the activity, indicating an improvement in participants’ overall capacity. The highest increase occurred in the knowledge aspect, followed by skills, while attitudes and perceptions were further strengthened. These findings indicate that practice-based training effectively supports community empowerment and the development of bamboo-based non-timber forest product enterprises.